Under-nutrition more in male children: a new study - Qadri, Henna Ahmadi; Srivastav, Shashank Kumar (International Journal of Research in Medical Sciences, 2017)
Background: A child’s entire life is determined in large measures by food intake during the growing age. Since childhood is the most vulnerable phase in the life of human being, nutritional inadequacies will result in hampering of growth as well as development of body. Future of the Country is determined by the growing generation. Methods: Total number of children aged 1-10 years is 1232 that attended Pediatrics out – patient department in the year 2013-14. The entire children aged 1-10 years were included in the study. Parents or/and guardians of the children were informed about the study. Weight of the children was measured using a portable weighing machine. Grading of nutritional status among 1-10 years old children was assessed by computing weight-for-age according to Indian Academy of Pediatrics classification. Results: Prevalence of under-nutrition (<80 percentage of standard weight-for-age) was 62.26%. The normal were 37.74%. The prevalence of Grade I malnourished was 29.30%, Grade II 19.49%, Grade III 9.25% and that of Grade IV was 4.22%. Prevalence of under-nutrition was higher among male (32.63%) than of female (29.62%) children. Conclusions: Nutritional status of children has been recognized as an important of National development which in turn depends on social development indices. Though the country is developing fast with wide availability of resources and food we still notice under-nourishment. Health education to the parents, especially to the mothers on dietary practices like feeding their children with healthy food in terms of quality and quantity should be given. Nutritional rehabilitation centre should be established which will guide the parents in regard to the nutrition of child to be maintain at particular growing age group. The finding of prevalence of under-nutrition in males is unique in Indian context where females are prone to get neglected and sex wise prevalence of under nutrition was usually higher in females as compared to males.